The transportation efficiency of cargo truck drivers from Thailand to Lao PDR - Sukanya Sirimat; Sakkarin Nonthapot (Journal of Project Management)
The purposes of this study are to study (1) opinions on the driving performance of cargo truck drivers and (2) the factors that affect the efficiency of driving cargo trucks from Thailand to the Lao PDR by crossing the first Thai-Lao Friendship Bridge. The study was conducted with a sample of truck drivers who transport goods across the Thailand border to Lao PDR at the Nong Khai Customs Area, Nong Khai Province. 384 respondents were acquired by selection according to their convenience. They then completed a questionnaire with confidence values between 0.70 – 0.90. The statistical data analysis for this study included mean and standard deviation, and structural equation analysis. The results showed that: (1) Truck drivers have various opinions on the personal factors of truck drivers; truck driver performance factors and truck driver transportation efficiency indicators are as follows: speed, economy, safety, comfort and punctuality factors, which are at very high levels and (2) The personal factors of a truck driver have a positive influence on truck driver performance while the truckers’ transportation efficiency and the truck drivers’ performance have positive influences on the efficiency of truck drivers' transportation by 54 percent.